Evaluating the Performance of Local Governments in Kwara State Post-Supreme Court Electoral Enforcement - Mohammed Idris Danjuma; Abdullahi, Abdulkarim Birogi.; Emmanuel O. Lambe (Journal of Public Administration and Government, 2025)
In Nigeria’s federal system, the local government tier has historically functioned under severe structural and political subordination, largely due to its entanglement with state-level controls. Despite constitutional provisions, decades of practice saw the widespread use of unelected caretaker committees, eroding democratic legitimacy and service delivery at the grassroots. Responding to growing public discontent and judicial activism, the Supreme Court in 2023 ruled that state governments must conduct proper local government elections or risk forfeiture of federal allocations. This judgment marked a watershed moment for local governance reform. However, one year after the enforcement of this autonomy, the actual impact remains contested. While elected officials now occupy local councils, widespread concerns persist about whether this structural shift has translated into meaningful administrative independence, fiscal transparency, or improved responsiveness. This study addresses this gap by examining how local governments in Kwara State specifically in Ilorin Metropolis, Offa, and Moro LGAs have fared since the reforms. Using a mixed-methods approach, the study gathered both qualitative and quantitative data from 400 respondents, including the general populace and local/state officials. Findings indicate significant perceptual differences regarding the fairness of elections and the autonomy in fiscal matters, while broader governance outcomes are viewed similarly across groups. The analysis reveals that structural reforms, while symbolically important, are insufficient without complementary measures such as institutional safeguards, civic oversight, and electoral transparency. The paper concludes by recommending legal and administrative reforms that deepen autonomy, promote fiscal accountability, and strengthen citizen engagement to ensure that electoral legitimacy is matched by functional and developmental governance at the grassroots.